A Psychological Study of the Main Character in the Seher Movie: Sigmund Freud Perspective - Setiawan, Budi; Naharudin, Naharudin; Ramdan, Zamroni; Humairo, Baiq Nuri (LPPM Universitas Bumigora Mataram, 2025)
This study examines Burhan’s psychological transformation in the movie “The Vengeance of Seher” using the psychoanalytic theory of Sigmund Freud’s Id, Ego, and Superego. Qualitative descriptive research was applied with the information gathered from dialogue or sentences regarding the movie’s main figure. The results of the study showed that the psychological pressure and rejection that the main figure received made the Id’s urge more dominant, causing him to take a shortcut by using black magic. His inability to control his inner conflict pushed him towards destructive actions, ultimately negatively impacting him and those around him. The film Seher not only presents horror elements, but also depicts how psychological disorders can affect a person’s behavior. Furthermore, this investigation provides insight into the importance of balance between the Id, Ego, and Superego in managing emotional stress. This study suggests that by comprehending fictional characters’ psychological aspects, audiences could become more aware of mental health concerns and emotional control. This study suggests that by comprehending the psychological aspects of fictional characters, the audience could grow more aware of mental health concerns and emotional control. Moreover, this research recommends additional studies employing different psychological techniques in addition to audience reaction analysis.